Pengaruh Kepemimpinan Karismatik Bambang H. Widjaja Terhadap Kesetiaan Melayani dari Volunteer Usher Doa Oasis GKPB Bandung - Samuel Dave Bobangu; Panca Parulian S; Royke Tumbelaka (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
The volunteers of ushers at Oasis Prayer show interesting facts: most of them are elderly mothers; not only that, some of them also have jobs, but they still choose to be loyal to be involved in service at Oasis Prayer. The author suspects that the loyalty of serving the Oasis prayer usher volunteers is due to the influence of Bambang Widjaja's charismatic leadership style as an elder at GKPB Fajar Pengharapan. To prove this assumption, the author conducted this research. This research uses quantitative methods, specifically a survey delivered to 30 volunteer ushers at Oasis Prayer, and shows the research results that first, Bambang Widjaja is a charismatic leader according to the volunteer ushers; secondly, the volunteer ushers at Oasis Prayer are loyal servants; and third, the loyalty of the volunteer ushers at Oasis prayer is influenced by the charismatic leadership of Dr. Bambang Widjaja. So that it produces a hypothetical conclusion, HA is accepted, and H0 is rejected, namely that Bambang Widjaja's charismatic leadership influences the loyalty of the Oasis prayer ushers at GKPB Fajar Pengharapan in 2022.